DISRUPTIVE TECHNOLOGIES FOR EDUCATIONAL INNOVATION IN DELTA STATE AND ITS CYBER SECURITY IMPLICATIONS: A POST COVID-19 ASSESSMENT - Okpako, Abugor Ejaita; Isitor, Nkechi; Ojie, Deborah Voke; Ukadike, Destiny (FUDMA JOURNAL OF SCIENCES, 2024)
Technology is everywhere and it’s changing the way things work, hence it is disruptive depending on its application and context. Disruptive technology introduces new markets and modifies existing ones, providing end users with better access, convenience, empowerment, choice, and value as well as competing with established models and practically transforming products and services. The COVID-19 pandemic necessitated a rapid shift to remote learning and the adoption of disruptive technologies in educational institutions worldwide, including Nigeria. Despite this, there is limited evidence investigating how different disruptive technologies and configurations associate with cyber security within the educational sector. This research work examines the association of disruptive technology and cyber security implications in the Delta State educational system during the post COVID 19 pandemic period. A cross sectional approach was used for data collection through questionnaires where 55 responses out of 80 respondents from some selected schools in Delta State were used. The results confirm some cyber threats on using disruptive technology in e-learning as phishing and identity theft. The respondent’s level of online satisfaction, cyber security awareness and performance was significantly associated with various independent variables such as e-learning platforms, online interaction, and privacy concerns. An understanding of these relationships will help educators and other stakeholders to prioritize legislation and regulations that will address such developments. The aim should not to over-regulate and consequently strangle them, but to envisage change, prepare for it, and set up appropriate regulatory frameworks to ensure societal balance.